THE IDEOLOGY IN THE INDONESIAN-TO-ENGLISH TRANSLATION OF CULTURAL TERMS IN TOER’S BUMI MANUSIA (English Education Journal, 2015)
The focus of translation has shifted from the macro level of isolated linguistic units to the macro level of the socio-cultural context in which the translation act takes places. It means that translation has played quite significant role in communicating and exchanging social and cultural information. The aim of this study is to find out the cultural terms in the Indonesian novel Bumi Manusia, the techniques of translation applied by the translator, and to explain how the techniques applied reflect the ideology of translation. The method of collecting data in this study was through observing by note-taking technique. The collected data were analyzed descriptively using qualitative method. There were 187 data of five categories of cultural terms, fourteen idioms, four sayings, and fourteen techniques identified in the novel. The most tendency of application of ideology of translation in translating the cultural terms related to Javanese culture was domestication ideology (78, 20%), it showed that the translation was oriented to TL. The next orientation used in the translation of the cultural terms was followed by foreignization ideology 12%), it showed that the translator tried to introduce Javanese cultural terms to the target readers using SL-oriented. The last tendency was partial foreignization and partial domestication (10,8%), it showed that the translation was partially oriented to SL and partially oriented to TL.